(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article analyzes the linguistic and cultural features of phrases containing the concept “book” in English and Uzbek languages. The study explores how both languages conceptualize and express the notion of a book through idioms, proverbs, and stable word combinations. While English expressions often emphasize knowledge, individuality, and intellect, Uzbek phrases highlight spirituality, morality, and lifelong respect for learning. The findings reveal that the concept of book serves as a cultural symbol of wisdom, morality, and civilization in both languages, though framed through distinct worldviews.